Análisis y evaluación de la seguridad de instalaciones y equipamientos deportivos escolares en la ciudad de Mérida (Extremadura) - Luis del Campo, Vicente (2016)
The aim of this study is to analyze the security (1= Fulfilled, 0= Not fulfilled) of sport facilities and equipments of schools in Merida, in accordance with NIDE and UNE-EN regulations. Additionally, their use was also assessed (1= Yes, I would use it, 0= No, I would not use it), the risk and the general state of conservation (scale from 1 to 5). All variables are recorded according to the check list developed by Herrador and Latorre (2008). 24 schools were analyzed, resulting in a total of 2611 items filled. The results show a safety average percentage of 54%, with an utilization rating of 85%. In addition, the risk assessment and the state of conservation reaches 2.26 and 3.71 respectively. There are differences in the study variables according to the type of sport facilities, equipment, and educational stage. Notably, the indoor facilities have higher security percentage (69%) and conservation assessment (3.67) while the outdoor ones have higher risk assessment (2.52). Baskets are the safest equipment (53%) with the highest conservation (4). Elementary-Secondary schools show the highest values of conservation (4.19) and the lowest levels of risk (1.95). It is recommended to enhance safety measures in the management and use of sport facilities and equipments at schools because the practice of sport and physical activities is not fully guaranteed in terms of safety.